NAGAN RAYA DISTRICT ATTORNEY'S OFFICE COMMUNICATION STRATEGY IN BUILDING A COMMUNITY IMAGE THROUGH SOCIAL MEDIA - Mulfida; Maulida, Desi (Transpublika Publisher, 2022)
The existence of social media cannot be separated from everyday life because it has become part of human life, both personal and agency, both private and government. They are competing to make information technology using various types of social media because social media has extraordinary benefits. is a great opportunity for the Nagan Raya District Attorney who presents the people. The Nagan Raya District Attorney can get closer to the people through social media, both to socialize activities, absorb information and aspirations, as well as communicate exclusively to find out the people's wishes. Related to that, conduct a study with the title of the Nagan Raya Public Prosecutor's Communication Strategy in Building the Image of the Community Through Social Media. The purpose of this study is to find out how the strategies and steps have been taken by the Nagan Raya District Attorney in building an image of the community through social media. So far public perception of the prosecutor's office well. This study uses a qualitative descriptive method of in-depth data collection from interviews with several informants, field observations and studies of documents related to objects that are used as references for the Nagan Raya District Attorney as part of the Regional Government in the use of social media to build a positive image of society. The results showed that the use of social media as a tool to increase the positive image of the Nagan Raya District Attorney was quite good.